Perancangan Interior Bowling dan Billiard Club di Surabaya - Mariana Wibowo, Jacky Santosa (Intra, 2014)
Bowling and Billiard Club is a form of recreation that could accommodate the communitys needs, especially Surabaya. As the information spread and peoples interest to try something new rise, availability of functional Bowling and Billiard facility is needed. Hence, appears the idea to provide a recreational and sport facility which applies